2023
DOI: 10.2147/ndt.s417676
|View full text |Cite
|
Sign up to set email alerts
|

Reintroducing Fenfluramine as a Treatment for Seizures: Current Knowledge, Recommendations and Gaps in Understanding

Gianluca Dini,
Giuseppe Di Cara,
Pietro Ferrara
et al.

Abstract: Despite the introduction of new anti-seizure medications in recent years, approximately one-third of the epileptic population continues to experience seizures. Recently, the anti-obesity medication fenfluramine (FFA) has been successfully repurposed, and it has received approval from various regulatory agencies for the treatment of seizures associated with Dravet syndrome and Lennox-Gastaut syndrome. The potential antiseizure effects of FFA were initially observed in patients with photosensitive epilepsy in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 91 publications
1
2
0
Order By: Relevance
“…Consistent with the findings reported by Damavandi et al ( 41 ), our meta-analysis observed a significant reduction in seizure frequency among patients treated with fenfluramine, reinforcing the drug’s efficacy in managing DS and LGS. Furthermore, our dose-specific analysis echoes the discussions by Dini et al ( 42 ) on the critical need for tailored treatment approaches, particularly in optimizing dosing regimens to balance efficacy with safety. When concentrated on different doses of FFA, 0.7 mg/kg/d FFA was more effective than 0.2 mg/kg/d FFA in reducing at least 75% seizure frequency.…”
Section: Discussionsupporting
confidence: 62%
“…Consistent with the findings reported by Damavandi et al ( 41 ), our meta-analysis observed a significant reduction in seizure frequency among patients treated with fenfluramine, reinforcing the drug’s efficacy in managing DS and LGS. Furthermore, our dose-specific analysis echoes the discussions by Dini et al ( 42 ) on the critical need for tailored treatment approaches, particularly in optimizing dosing regimens to balance efficacy with safety. When concentrated on different doses of FFA, 0.7 mg/kg/d FFA was more effective than 0.2 mg/kg/d FFA in reducing at least 75% seizure frequency.…”
Section: Discussionsupporting
confidence: 62%
“…Fenfluramine is a recently approved drug that has high efficacy for the treatment of seizures in Dravet syndrome and Lennox–Gastaut syndrome [ 75 ]. Studies have shown that fenfluramine exerts its anticonvulsant effects by enhancing serotonergic transmission through various receptors, including the 5-HT1A receptor [ 44 , 76 ]. Here, we investigated whether CBD exerts its anticonvulsant effects through the 5-HT1A receptor.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic approach in DS focuses on polytherapy, involving the use of multiple anticonvulsant medications, as well as the implementation of the ketogenic diet (Riva et al, 2022 ; Dini et al, 2023 ). Furthermore, some invasive methods, such as vagus nerve stimulation have been also proposed, although a definitive consensus on their efficacy has not been reached so far (Wirrell et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%